Characterization of 3D oxygen concentrations in hydrogels combining astigmatic particle tracking with phosphorescence decay measurements - Werner, Mayke; Schmidt, Mareike; Etzold, Bastian; Fritschen, Anna; Blaeser, Andreas; Hussong, Jeanette (Experiments in Fluids, 2025)
In this work, we combine astigmatic particle tracking with phosphorescence decay measurements to determine 3D oxygen concentration distributions in microfluidic systems. Out-of-plane positions are reconstructed to an accuracy of 1.5 μ μ m. The calibrated measurement range covers oxygen concentrations between 0.6 to 27.6 ppm. A method is presented to systematically correct for measurement errors caused by photobleaching taking into account the excitation energy, the cumulative laser irradiation time and the spatially varying intensity profile of the laser. With this method, low measurement errors of less than 2 ppm at ambient oxygen levels can be achieved even after thousands of excitation cycles. To demonstrate the capability of the measurement technique, 3D oxygen concentrations are measured in an agarose hydrogel filled microfluidic chamber across which different pressure and oxygen gradients can be set independently. The results show that oxygen diffusion is superposed by a convective transport of interstitial flow. By matching numerical simulations to the experimental data, further insights into the ratio of convective and diffusive transport are given and a methodology for estimating relevant material parameters is presented. This in situ measurement technique can be applied to improve the design process of supply networks for tissue model